Simulation of The Number of Microbial Populations For Fertility Optimization In Clay Soils Using Smart Biosoidam Technology - Nugroho Widiasmadi (Syntax Literate, 2022)
This research was conducted on clay soils, especially for vegetable plantations, aimed to determine the ability of the soil layer to distribute nutrients and restore soil health and fertility due to the use of chemical fertilizers and pesticides. Through microbial activity that is controlled by spreading through a horizontal biohole, this study observes in real time through a micro controller the changes in soil acidity, infiltration rate, electrolyte conductivity levels and porosity levels through soil infiltration rates. Through simulations with the variable microbial population, it can be seen the level of EC and other parameters against the time of observation in real time. From the observations of graphs and EC standards, it can be seen that the ability of the soil to because until day 45 the soil fertility level has not reached = 1500 uS / cm with a microbial population = 103/ cfu. support the planting schedule both during the vegetative growth period and during the generative growth period, so that we will know when is the right time to do: soil recovery, initial planting and when the tubers / flowers / fruit begin to be conditioned. until cooked based on nutrient values observed through sensors that convert analog parameters by the micro controller into digital information transmitted by wifi in real time. The initial condition before simulating the soil fertility value with the Electrolyte Conductivity (EC) parameter is 744 uS / cm, the simulation results are: Simulation 1: nutrient content for generative growth was achieved on day 27 with fertility level = 1525 uS / cm with Microbial Population 10 8 / cfu. Simulation 2: nutrient content for generative growth was achieved on day 42 at the fertility level = 1500 uS / cm with microbial population = 10 5/ cfu. Simulation 3: nutrient content for generative growth cannot be observed